Splendori e miserie di un copista filosofo. Cinico a Napoli dopo gli Aragonesi (Carte Romanze, 2025)
The article investigates the last years of life and activity of the famous copyist and vernacularizer Giovan Marco Cinico (ca. 1430-post 1503), who was for about forty years in the service of the Aragonese rulers in Naples. Some hitherto neglected data, including a letter sent to king Manuel I of Portugal in 1514, are presented.
Keywords: Giovan Marco Cinico; Naples; cynicism; Manuel I of Portugal; Giano Anisio; Cosimo Anisio